2019
DOI: 10.1016/j.aott.2019.08.016
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanical effects of sequential resection of the posterior ligamentous complex on intradiscal pressure and resistance to compression forces

Abstract: ObjectiveThe aim of this biomechanical experimental study was to evaluate the resistance of each posterior ligamentous complex structure of the thoracic and lumbar spine to compression forces and to measure the shifting load to the intervertebral disc when each PLC structure was interrupted.MethodThe study was conducted on 4 groups for thoracic and lumbar region as intact, supraspinous ligament interrupted, interspinous ligament/ligamentum flavum combination interrupted and facet joint capsule interrupted. Pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…Multiple clinical investigations have showed that congenital malformations of spine (including scoliosis, kyphosis, spina bifida, spondylolysis and Klippel Feil syndrome) 35,36 , accidental back injury or ligament injury [37][38][39] , occupational exposure (such as crane and car drivers, weightlifters, etc.) [40][41][42] could induce aberrant mechanical loading of lumbar spine, and finally lead to IVDD.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple clinical investigations have showed that congenital malformations of spine (including scoliosis, kyphosis, spina bifida, spondylolysis and Klippel Feil syndrome) 35,36 , accidental back injury or ligament injury [37][38][39] , occupational exposure (such as crane and car drivers, weightlifters, etc.) [40][41][42] could induce aberrant mechanical loading of lumbar spine, and finally lead to IVDD.…”
Section: Discussionmentioning
confidence: 99%
“…The spinous processes, interspinous ligament, and part of the posterior ligamentous complex play a role in spinal stability 29 . After spinal surgery, osseous continuity between the spinous processes and the lamina is important for maintaining the long‐term benefit 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Severity of PLC injury is believed to correlate with subsequent potential for instability, deformity and neurological compromise. 15 , 16 CT scans can be used to indirectly evaluate PLC integrity; MRI can add accuracy to the assessment. 17 …”
Section: Discussionmentioning
confidence: 99%
“…Severity of PLC injury is believed to correlate with subsequent potential for instability, deformity and neurological compromise. 15,16 CT scans can be used to indirectly evaluate PLC integrity; MRI can add accuracy to the assessment. 17 The AOSpine Thoracolumbar Spine Injury Classification System has previously been found to have good inter-and intraobserver reliability and reproducibility in the adult population.…”
Section: Discussionmentioning
confidence: 99%